An Efficient and Scalable Semiconductor Architecture for Parallel Automata Processing - Dlugosch, Paul; Brown, Dave; Glendenning, Paul; Leventhal, Michael; Noyes, Harold (IEEE transactions on parallel and distributed systems, 2014)
We present the design and development of the automata processor, a massively parallel non-von Neumann semiconductor architecture that is purpose-built for automata processing. This architecture can directly implement non-deterministic finite automata in hardware and can be used to implement complex regular expressions, as well as other types of automata which cannot be expressed as regular expressions. We demonstrate that this architecture exceeds the capabilities of high-performance FPGA-based implementations of regular expression processors. We report on the development of an XML-based language for describing automata for easy compilation targeted to the hardware. The automata processor can be effectively utilized in a diverse array of applications driven by pattern matching, such as cyber security and computational biology.